2017
DOI: 10.1038/s41598-017-09006-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infections in hospitalized children in Vientiane, Lao PDR – the importance of Respiratory Syncytial Virus

Abstract: The Human respiratory syncytial virus (RSV) is one of the most important viral pathogens, causing epidemics of acute respiratory infection (ARI), especially bronchiolitis and pneumonia, in children worldwide. To investigate the RSV burden in Laos, we conducted a one-year study in children <5 years old admitted to Mahosot Hospital, Vientiane Capital, to describe clinical and epidemiological characteristics and predictive factors for severity of RSV-associated ARI. Pooled nasal and throat swabs were tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
4
23
2
Order By: Relevance
“…In Luang Prabang in 2010, the incidence of influenza A and B viruses was significantly associated with the rainy season; in 2010, the influenza season presented as a single wave with a peak in September and declined in October‐November, similar to other regions in Lao PDR during the same year . Also RSV was mostly found during the rainy season in Luang Prabang in 2010, similarly to Thailand, Vietnam, Cambodia and to Vientiane in 2009‐2010 and 2014 . In contrast, other respiratory viruses (hAdV, hBoV, hMPV, hCoV‐HKU1, hCoV‐OC43, and PIV3) occurred more often during the dry season, causing respiratory disease mainly when influenza and RSV were less present, while PIV1‐2, hRV, and hCoV‐229E were detected throughout the year, contributing to the background incidence of respiratory infections .…”
Section: Discussionmentioning
confidence: 93%
“…In Luang Prabang in 2010, the incidence of influenza A and B viruses was significantly associated with the rainy season; in 2010, the influenza season presented as a single wave with a peak in September and declined in October‐November, similar to other regions in Lao PDR during the same year . Also RSV was mostly found during the rainy season in Luang Prabang in 2010, similarly to Thailand, Vietnam, Cambodia and to Vientiane in 2009‐2010 and 2014 . In contrast, other respiratory viruses (hAdV, hBoV, hMPV, hCoV‐HKU1, hCoV‐OC43, and PIV3) occurred more often during the dry season, causing respiratory disease mainly when influenza and RSV were less present, while PIV1‐2, hRV, and hCoV‐229E were detected throughout the year, contributing to the background incidence of respiratory infections .…”
Section: Discussionmentioning
confidence: 93%
“…HRSV prevailed (67.98%) in younger infants (0 to ≤6 months), while HADV was prevalent in all other age groups studied. Accordingly, HRSV causes severe diseases in young children (Moe et al, 2017;Nguyen et al, 2017;Shi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although lower prevalence rates have been reported in Korea (2.7%) ( Noh et al, 2013 ) and Brazil (2.4%) ( Bellei et al, 2008 ), RSV infection is reportedly frequent in western China (23.7%) ( Hu et al, 2017 ), the Philippines (19.3%–28.1%) ( Ohno et al, 2013 ; Malasao et al, 2015 ), Vietnam (23%) ( Yoshida et al, 2010 ), Indonesia (23%) ( Simões et al, 2011 ), and Malaysia (18.4%) ( Chan et al, 2002 ). A recent single hospital study in Laos identified RSV in as many as 41% of infected children ( Nguyen et al, 2017 ). Unfortunately, objective comparison of the true regional prevalence of RSV is often hindered by the differences in the RSV detection rates largely due to sample size and the period of surveillance among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in RSV infection depends on geographical region, season, and year. In Southeast Asia, RSV incidence appears to peak during the rainy season (July to November), while relatively low rate of infection occurs during the hot and dry months ( Arnott et al, 2011 ; Nguyen et al, 2017 ; Yoshida et al, 2010 ). This is in contrast to the peak incidence in countries with temperate climates whereby RSV infections are more frequent in the winter months ( Gilca et al, 2006 ; Panayiotou et al, 2014 ; Esposito et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%